Servant leadership as part of spiritual formation of theological students in contextualisation of 21st century theological training - Plessis, Amanda L. du (HTS teologiese studies, 2020)
The theory of servant leadership with its key concepts of servanthood and leadership has emerged during the last few decades. A person who has a heart for people and serves them whilst leading them practices servant leadership. Servant leaders are not motivated by attaining higher positions but by serving people. Leaders call people to follow a set vision. In the church, that vision ought to be a God vision, premised on the Word of God. Leaders in the church should lead people according to the guidance of the Bible and inspiration from God. He is the one who calls people, gives them an assignment and will require an account from them. The church has been in the spotlight in recent times because of the conduct of their leaders, who are the pastors assigned with the task of leading believers. Understanding the principles of servant leadership can contribute to spiritual formation of theological students in contextualisation of 21st century theological training. The article begins with a reflection on the findings of an empirical study, followed by a short view on the servant leadership of Moses, David, Paul and Jesus Christ. Thereafter, the article focuses on servant leadership characteristics and competencies or skills according to contemporary scholars, and the article concludes with a proposed model for servant leadership as part of spiritual formation of theological students.Contribution: Although the article is context specific to the Faculty of Theology, Mahikeng campus, the principles of servant leadership can contribute to the spiritual formation of all theological students and is especially relevant to the discourse of contextualised 21st century theological training.